LANGUAGE AND CULTURE: DYAD AND UNITY - A. L. Semenov; V. I. Ershov; D. A. Gusarov (Vestnik MGIMO-Universiteta)
This paper deals with the concept of the translation approach to the problem of interaction of language and culture in terms of determination of the translation solutions by linguoethnic factors. The authors pay main attention to the analysis of the notion of culture. The concept proceeds from the views and opinions regarding the culture and its role in shaping the identity of the person introduced by the honorary doctor (doctor honoris cause) of the MGIMO-University Federico Major in his book «New page». Sharing the point of view of F. Major , the authors come to the conclusion that culture is a knowledge, based on which an individual perceives and evaluates his performance and behavior. Projecting such a position on the verbal behavior, the authors highlight the leading role of culture in the process of producing a speech act played when choosing the individual models of behavior on the basis of the knowledge of the communicative situation. Based on F. Mayor`s opinion that culture unites rather than divides people, the authors note the presence of universal and unique linguoethnic elements in the cultural knowledge of the representatives of various ethnic groups which determine the degree of similarities and differences in the ways of expressing knowledge in different languages. In this paper the authors reasonably use the term «linguoethnic» to describe the cultural-cognitive peculiarities inherent to individuals as representatives of different ethnic groups, as well as give comparison of the terms «linguoethnic» and «linguocultural».